An in vitro and in silico identification of antibiofilm small molecules from seawater metaclone SWMC166 against Vibrio cholerae O1. (June 2018) - Rajalaxmi, Murugan; Beema Shafreen, Rajamohamed; Chithiraiselvi, Karuppiah; Karutha Pandian, Shunmugiah
Abstract: This study aimed to determine the antibiofilm activity of seawater microbes against Vibrio cholerae (VCO1) through functional metagenomics approach. A metagenomic library was constructed from Palk Bay seawater and the library was screened to identify the biofilm inhibitory metaclone. Metaclone SWMC166 (harbouring ∼30 kb metagenomic insert) was found to exhibit antibiofilm activity against VCO1. The biofilm inhibitory potential of partially purified ethyl acetate extract of SWMC166 (EA166) was further evaluated through microscopic studies and biochemical assays. Further, EA166 treated VCO1 divulged up-regulation of genes involved in high cell density-mediated quorum sensing (QS) pathway which was analysed by real-time PCR. In order to identify the genes of interest (within ∼30 kb insert), subcloning was performed through shotgun approach. Small molecules from positive subclones SC5 and SC8 were identified through HRLC-MS analysis. Resulted small molecules were docked against QS receptors of V. cholerae to identify the bioactive metabolites. Docking studies revealed that totally seven metabolites were able to interact with QS receptors that can possibly trigger the QS cascade and sequentially inhibit the biofilm formation and virulence factors of VCO1. Graphical abstract: Highlights: The metaclone SWMC166 exhibited antibofilm activity against Vibrio cholerae O1. The antibiofilm activity was confirmed through in vitro and real time PCR assays. Subcloning was performed to identify the gene responsible for antibiofilm activity. Bioactives from subclones SC5 and SC8 were identified through HRLC-MS analysis. Docking studies evidenced the antibiofilm effect through modulation of QS pathway.